Effect of Melia extracts on oviposition, gonad development and field infestation of melon fruit fly (Bactrocera tau) in cucumber (Cucumis sativus) - SHARMA, MANOJ K; SHARMA, I D; SHARMA, K C (The Indian Journal of Agricultural Sciences, 2012)
Studies on the effect of darek (Melia azedarach L.) seed kernel extract (DSKE) in aqueous and bait forms on the oviposition, gonad development and field infestation of melon fruit fly (Bactrocera tau walker) in cucumber (Cucumis sativus L.) revealed that of the treatments evaluated under laboratory conditions, 2% aqueous DSKE gave maximum oviposition deterrence (79.1%) after 24 hr of treatment over control. The deterrent effect decreasing with time lasted for 168 hr. In bait treatments, mean number of eggs laid at 24 hr intervals after 144 hr was minimum (8.1 eggs/five females) in fruits treated with Bait IV (DSKE 2% + diet) as compared to 11.0 eggs in standard malathion bait and 24.3 eggs in control/24 hr. Upon dissection, it was found that fruit flies fed on Bait IV had significantly under developed ovaries measuring 1.9±0.06 × 1.7±0.03mm in size against 3.4±0.08 × 2.8±0.04mm in those fed on normal proteinaceous diet. Moreover, baits carrying higher concentration of DSKE than in Bait IV caused significant adult mortality. Among the concentrations tested, Bait VIII (DSKE 6.0% + diet) caused maximum mortality (59.1%) 24 hr after treatment. Under field conditions, fruit fly infestation was lowest (3.1%) in plots sprayed with Bait X (DSKE 12.0% + diet) against 11.1 and 64.8% in standard bait sprayed plot and the untreated, respectively. No phyto-toxic effects were observed. The Melia bait sprays proved more effective than standard malathion bait in the management of melon fruit fly and increasing the total crop yield.